Steamboat J.P. LIGHT in Five Finger Rapids, Yukon River, approximately 1898 - University of Washington Libraries. Special Collections Division. (1898)
Caption on image: Steamer passing up Five Finger Rapids Steamboat built by the Moran Brothers Co. and launched on April 23, 1898. Delivered to the British American Corporation at the mouth of the Yukon in May of that year. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number